"What Daughters, what Wives, what Mothers, Think You, They are?"2 Gender and the Transformation of Executions in the United States. Issue 2 (6th March 2014) - Linders, Annulla
Abstract The transformation from public to private executions is generally understood as a consequence of the rationalization of authority in conjunction with growing class tensions and the emergence of bourgeois sentimentality. What is missing from this analysis is the role gender played. The exclusion of women from the execution site captures a more general tension around womanhood in the nineteenth century, but that tension was expressed differently depending on women's class and race locations. Using newspaper coverage of executions as my primary data source, I show that the interpretive challenges posed by women at the execution site varied by the social positions they occupied.